Feeding Therapy in Preterm Infants - Ida Ayu Wulan Kartika Dewi Manuaba; Bagus Diva Indra Dharma (Faculty of Medicine, Universitas Airlangga, 2023)
Low Birth Weight (LBW) or Very Low Birth Weight (VLBW) infants often have feeding difficulty issues that impact feeding abilities, leading to complications such as difficulty gaining weight and prolonged length of stay (LOS) in the hospital. Early feeding therapy interventions have good outcomes for LBW or VLBW preterm in accelerating feeding goals, gaining weight, and reducing LOS. This article reported two cases of VLBW patients who were referred from the Pediatric Department to the Physical Medicine and Rehabilitation Department because of feeding difficulties that led to prolonged LOS, in order to achieve better outcomes in spontaneous oral feeding. The feeding therapy intervention was given to the infants every day by the speech therapist. Feeding therapy intervention shows promising results in provoking the proper sucking reflex in VLBW preterm infants, which helps them to achieve better oral feeding ability that accelerates weight gain and reduces LOS in the hospital.